KEPUTUSAN PEMBELIAN PRODUCT LIP CREAM HANASUI MELALUI CONTENT MARKETING, PERSEPSI HARGA DAN PACKAGING PRODUCT PADA MAHASISWA FAKULTAS EKONOMI BISNIS UNVIVERSITAS TEKNOLOGI SUMBAWA - Khairunnas, Fadlun Husnul; Ananda, Nova Adhitya (Publika Citra Media, 2025)
This study aims to analyze the factors that determine the purchasing decision of Hanasui lip cream among students of the Faculty of Economics and Business at Sumbawa University of Technology. The examined factors include content marketing, price perception, and product packaging. This research employs a quantitative descriptive method with a purposive sampling technique. Data was collected through questionnaires distributed to 100 respondents. Data analysis was conducted using the Three Box Analysis method. The results indicate that content marketing plays a significant role in shaping purchasing decisions, followed by price perception and product packaging. Effective marketing strategies, affordable pricing, and attractive packaging contribute to increased student purchasing decisions.